Zakat sebagai Distribusi Kekayaan - Mubarak, Sahrum (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Zakat in Islam is not only a spiritual obligation but also a crucial instrument for the fair distribution of wealth within society. Amid ongoing social and economic disparities in various regions, zakat serves as a bridge between the wealthy and the poor to create social balance. This study aims to examine the concept of zakat as a tool for wealth distribution through a qualitative approach based on literature review. By analyzing various sources from three primary journals, this research highlights the role of zakat in reducing poverty, promoting social justice, and supporting national fiscal policy. The findings indicate that zakat is effective in improving community welfare if managed professionally and transparently. However, challenges remain, including low public trust in zakat management institutions, weak regulatory frameworks, and limited public literacy on productive zakat. With strengthened fiscal policies and the integration of a modern zakat management system, the potential of zakat in wealth distribution can be maximized.